TEACHERS’ VOICES ON THE DEVELOPMENT OF STUDENTS’ NATIONAL IDENTITY THROUGH THE EMBEDDING OF LOCAL CULTURE - Masita, Ella; Hidayat, Marzul; Fortunasari, Fortunasari (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This paper investigates how Indonesian English language and science teachers in Jambi municipality perceive the relationship between national identity and local culture in English and Science teaching. Through thematic analysis, the study explores teachers’ understanding toward the role of national identity in English and Science teaching as well as the challenges and strategies teachers encounter in integrating national identity into their teaching practices by the inclusion of local culture, emphasizing the importance of Jambi cultural context in the teaching. The research results reveal a number of findings such as teachers’ beliefs that exploring national identity in the classroom can help students develop a sense of belonging and awareness of their place in a multicultural world. However, they express varying degrees of emphasis on national identity, with some advocating for a bigger portion of context of local culture, while others may prioritize students’ development of English mastery no matter what culture is embedded. Teachers also report challenges and strategies employed, for instance the conduction of collaborative learning to help students learn from each other’s perspectives, designing inclusive teaching materials to include diverse perspectives of national identity, and enhancing teachers’ understanding of cultural sensitivity and identity issues. To conclude, it is recommended to build adequate support for a balanced English and Science teaching designs that respect and celebrate national identity while, at the same time, be able to prepare students for global engagement. By fostering the integration of local and global perspectives, English and Science education in Indonesia will be able to create English and Science teaching environment that empowers students as both national and global citizens.